METHODOLOGICAL RECOMMENDATIONS FOR TEACHING ENGLISH TO CHILDREN 7-16 YEARS OLD - Feruzakhan Mirzakhmedova Abdumutalovna (American Journals, 2023)
This article provides information on the methods and recommendations of teaching English to schoolchildren aged 5 to 16 years
Keywords: learning, foreign language, natural mechanism, creative imagination